Balancing Forage and Legumes: Impact on Goat Feed Intake and Nutrient Digestibility - Rezki Ayu Ramadani; Asmuddin Natsir; Ismartoyo Ismartoyo (Journal of Global Innovations in Agricultural Sciences)
Goats play a vital role in livestock production systems, particularly in smallholder farming, providing valuable meat, milk, and fiber sources. However, maximizing goat productivity is contingent upon providing a balanced and nutritious diet. This study evaluated the impact of elephant grass-legume mixtures on nutrient consumption and digestibility in goats, aiming to identify the most effective combination for enhancing feed efficiency. Using a 4x4 Latin Square Design, four goats (14–25 kg) were fed four treatments: P1 (70% elephant grass + 30% Moringa), P2 (70% elephant grass + 30% Indigofera), P3 (70% elephant grass + 30% Lamtoro), and P4 (70% elephant grass + 30% Gamal). Key findings showed that the Lamtoro mixture (P3) achieved the highest nutrient consumption and digestibility, outperforming other treatments. Unlike previous studies, this research underscores the comparative advantages of specific legume combinations, with Lamtoro demonstrating significant potential as a superior forage option for small ruminants. These results highlight the critical role of balanced forage-legume mixtures in enhancing goat productivity and advancing sustainable livestock systems. Keywords: Elephant grass utilization, forage management, goat feeding strategy, sustainable agriculture, ruminant performance, nutritional digestibility, protein rich fodder.